Anti-pollution large-flux reverse osmosis (RO) membrane as well as preparation method and application thereof
By preparing a fouling-resistant, high-flux reverse osmosis (RO) membrane, and utilizing interfacial polymerization and surface functionalization modification, the problem of easy fouling of traditional reverse osmosis membranes has been solved, achieving a synergistic improvement in high flux and fouling resistance, making it suitable for various water treatment scenarios.
Patent Information
- Application Number
- CN202511731616.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-24
- Publication Date
- 2026-03-17
AI Technical Summary
Traditional reverse osmosis membranes are prone to fouling during long-term use, resulting in decreased membrane flux, shortened service life, increased operating costs, and limited application scope.
By limiting the formulation parameters of the aqueous and oil phase solutions, interfacial polymerization, and post-treatment conditions, a fouling-resistant, high-flux reverse osmosis (RO) membrane was prepared, forming a structurally stable polyamide separation layer. Antifouling functional groups, such as sulfonic acid groups, carboxyl groups, and polyether segments, were grafted onto its surface to enhance the membrane's hydrophilicity and antifouling properties.
It achieves a synergistic improvement in high flux and antifouling performance of reverse osmosis membranes, reduces flux decline caused by fouling, extends membrane lifespan, and lowers operating costs. It is suitable for seawater desalination, brackish water desalination, drinking water purification, and industrial wastewater reuse treatment.
Smart Images

Figure CN121669020A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application relates to the technical field of reverse osmosis membranes, in particular to an anti-pollution high-flux reverse osmosis (RO) membrane and a preparation method and application thereof. BACKGROUND
[0002] The reverse osmosis technology is widely applied in the fields of seawater desalination, brackish water desalination, drinking water purification and industrial wastewater reuse due to the high membrane separation capacity. However, the traditional reverse osmosis membrane is prone to pollution in long-term use, which is manifested in the decrease of membrane flux and the shortening of service life, thus increasing the operation cost and limiting the further expansion of the application range. Therefore, the application provides an anti-pollution high-flux reverse osmosis (RO) membrane and a preparation method and application thereof. SUMMARY
[0003] The application aims at solving the problems in the background art, and provides an anti-pollution high-flux reverse osmosis (RO) membrane and a preparation method and application thereof.
[0004] The specific technical scheme is as follows:
[0005] A preparation method of an anti-pollution high-flux reverse osmosis (RO) membrane comprises the following steps:
[0006] S1, preparing an aqueous solution: mixing a polyamine, an additive and water to obtain an aqueous solution, the additive being a substance capable of forming a complex with the polyamine and being removable in subsequent treatment, the mass fraction of the polyamine in the aqueous solution being 0.8% to 6%, and the mass fraction of the additive being 0.3% to 4%;
[0007] S2, preparing an oil solution: dissolving a polyacyl chloride in an organic solvent to obtain an oil solution, the mass fraction of the polyacyl chloride in the oil solution being 0.08% to 2.5%;
[0008] S3, interfacial polymerization: coating the aqueous solution on the surface of a support layer, removing the excess aqueous solution after standing, then coating the oil solution, and performing an interfacial polymerization reaction to form a polyamide separation layer, the time of the interfacial polymerization reaction being 10 to 60 seconds;
[0009] S4, post-treatment: performing heat treatment on the membrane after the formation of the polyamide separation layer, the temperature of the heat treatment being 80-120 DEG C, and the time being 1 to 5 minutes; after the heat treatment, the membrane is washed with deionized water for 30 minutes to remove the complex formed by the additive and the polyamine, then the membrane is immersed in a solution containing an anti-pollution functional monomer, so that the anti-pollution functional monomer and the polyamide separation layer surface perform a grafting reaction, the temperature of the grafting reaction being 20-60 DEG C, and the time being 0.5 to 3 hours, to obtain the anti-pollution high-flux reverse osmosis (RO) membrane; the anti-pollution functional monomer is a compound containing at least one of a sulfonic acid group, a carboxyl group and a polyether chain segment.
[0010] The preparation method of the anti-pollution high-flux reverse osmosis RO membrane adopts the technical scheme, by limiting the formula parameters of the water phase solution and the oil phase solution, the specific conditions of the interfacial polymerization and post-processing, especially the removal method of the additive and the grafting reaction of the anti-pollution functional monomer, the prepared reverse osmosis membrane can form a stable polyamide separation layer, and the surface is grafted with an anti-pollution functional group, so as to improve the hydrophilicity and anti-pollution property of the membrane, ensure a high flux, and realize the synergistic effect of anti-pollution and high flux.
[0011] The preparation method of the anti-pollution high-flux reverse osmosis RO membrane, wherein the polyamine is at least one of m-phenylenediamine and p-phenylenediamine, the additive is at least one of sodium hexametaphosphate and sodium tripolyphosphate, the mass fraction of the polyamine in the water phase solution is 1% to 5%, and the mass fraction of the additive is 0.5% to 3%.
[0012] The preparation method of the anti-pollution high-flux reverse osmosis RO membrane, wherein the polyamine is at least one of m-phenylenediamine and p-phenylenediamine, the additive is at least one of sodium hexametaphosphate and sodium tripolyphosphate, the mass fraction of the polyamine in the water phase solution is 1% to 5%, and the mass fraction of the additive is 0.5% to 3%.
[0013] The preparation method of the anti-pollution high-flux reverse osmosis RO membrane, wherein the polyamine is at least one of m-phenylenediamine and p-phenylenediamine, the additive is at least one of sodium hexametaphosphate and sodium tripolyphosphate, the mass fraction of the polyamine in the water phase solution is 1% to 5%, and the mass fraction of the additive is 0.5% to 3%.
[0014] The preparation method of the anti-pollution high-flux reverse osmosis RO membrane, wherein the polyamine is at least one of m-phenylenediamine and p-phenylenediamine, the additive is at least one of sodium hexametaphosphate and sodium tripolyphosphate, the mass fraction of the polyamine in the water phase solution is 1% to 5%, and the mass fraction of the additive is 0.5% to 3%.
[0015] The preparation method of the anti-pollution high-flux reverse osmosis RO membrane, wherein the polyamine is at least one of m-phenylenediamine and p-phenylenediamine, the additive is at least one of sodium hexametaphosphate and sodium tripolyphosphate, the mass fraction of the polyamine in the water phase solution is 1% to 5%, and the mass fraction of the additive is 0.5% to 3%.
[0016] The preparation method of the anti-pollution high-flux reverse osmosis RO membrane, wherein the polyamine is at least one of m-phenylenediamine and p-phenylenediamine, the additive is at least one of sodium hexametaphosphate and sodium tripolyphosphate, the mass fraction of the polyamine in the water phase solution is 1% to 5%, and the mass fraction of the additive is 0.5% to 3%.
[0017] The preparation method of the anti-pollution high-flux reverse osmosis (RO) membrane, wherein, before the interface polymerization step, a pretreatment step of the support layer is further included, the pretreatment is immersing the support layer into a solution containing a coupling agent, the coupling agent is at least one of a silane coupling agent and a titanate coupling agent, the mass fraction of the coupling agent solution is 0.1% to 2%, and the soaking time is 5 to 30 minutes.
[0018] By adopting the technical scheme, the support layer and the polyamide separation layer are combined with high strength by the coupling agent, the risk of interlayer peeling of the membrane during use is reduced, and the mechanical stability and service life of the membrane are improved.
[0019] The application further provides an anti-pollution high-flux reverse osmosis (RO) membrane prepared by the preparation method, comprising a support layer and a polyamide separation layer arranged on the surface of the support layer, the surface of the polyamide separation layer is grafted with anti-pollution functional groups with hydrophilicity and anti-pollution property, the anti-pollution functional groups are groups containing at least one of a sulfonic acid group, a carboxyl group and a polyether segment formed after grafting of anti-pollution functional monomers, and the surface roughness Ra of the polyamide separation layer is less than 0.5 nm, and the absolute value of the Zeta potential of the membrane surface is less than 10 mV.
[0020] By limiting the layer structure of the reverse osmosis membrane and the characteristics of the anti-pollution functional groups, and the range of the surface roughness and the Zeta potential, the membrane surface has a low tendency of adsorbing pollutants, while the compactness of the separation layer is ensured, and the balance between the anti-pollution performance and the separation performance is achieved.
[0021] The anti-pollution high-flux reverse osmosis (RO) membrane, wherein the support layer is a polysulfone support layer, the thickness of the polysulfone support layer is 50-150 μm, and the polysulfone support layer contains nano titanium dioxide particles with a mass fraction of 0.5% to 3%.
[0022] By limiting the support layer to be a polysulfone support layer containing nano titanium dioxide particles and the thickness range, the nano titanium dioxide particles can enhance the mechanical properties and anti-aging properties of the support layer, the polysulfone material itself has good chemical stability, and the combination of the two can improve the overall structural strength and weather resistance of the membrane.
[0023] The anti-pollution high-flux reverse osmosis (RO) membrane, wherein the thickness of the polyamide separation layer is 50-200 nm, and the grafting density of the anti-pollution functional groups on the surface of the polyamide separation layer is 0.1-1 μmol / m².
[0024] By adopting the above technical solution, by limiting the thickness of the polyamide separation layer and the grafting density of the antifouling functional groups, a suitable thickness can ensure the separation efficiency of the membrane, and an appropriate grafting density can improve the antifouling performance while avoiding adverse effects on the membrane flux, thus achieving optimization of antifouling and high flux.
[0025] This invention also provides an application of a high-flux, anti-fouling reverse osmosis (RO) membrane in seawater desalination, brackish water desalination, drinking water purification, and industrial wastewater reuse treatment.
[0026] By adopting the above technical solution, and utilizing the antifouling and high-flux characteristics of membranes, it can adapt to different water quality conditions in water treatment fields such as seawater desalination and brackish water desalination, reduce system downtime and maintenance caused by membrane fouling, and improve water treatment efficiency.
[0027] The above-mentioned antifouling high-flux reverse osmosis (RO) membrane is used in seawater desalination, brackish water desalination, drinking water purification, and industrial wastewater reuse. When using the antifouling high-flux reverse osmosis RO membrane for water treatment, the turbidity of the influent is less than 1 NTU, the SDI value is less than 5, and during the treatment process, the membrane is chemically cleaned every 1-3 months. The cleaning agent used for chemical cleaning is an acidic or alkaline cleaning agent with a pH value of 2-12, and the cleaning agent contains 0.1% to 2% surfactant by mass.
[0028] By adopting the above technical solution and clarifying the influent water conditions and chemical cleaning methods during membrane use, the damage of influent pollutants to the membrane can be reduced. Regular chemical cleaning can effectively restore membrane performance, extend the membrane's operating cycle, and reduce water treatment costs.
[0029] The present invention has the following beneficial effects:
[0030] By precisely controlling the preparation process parameters, including the concentrations of the aqueous and oil phase solutions, the interfacial polymerization time, the heat treatment conditions, and the grafting parameters of the antifouling functional monomers, the membrane achieves a synergistic improvement in multiple properties.
[0031] Due to its thorough interfacial polymerization and uniform structure, the polyamide separation layer exhibits excellent separation performance, effectively retaining salt and contaminants in water. The introduction and removal of additives optimize the membrane's microstructure, and combined with the grafting of antifouling functional groups, it significantly enhances antifouling performance while increasing membrane flux, reducing flux decline caused by fouling.
[0032] Pretreatment of the support layer enhances the mechanical stability of the membrane and extends its service life. The overall solution, through the coordinated design of each component, balances the membrane's separation efficiency, flux, and antifouling performance, solving the problems of easy fouling and low flux in traditional reverse osmosis membranes. It is suitable for various water treatment scenarios, reducing operating costs and improving water treatment efficiency. Attached Figure Description
[0033] Figure 1 A flowchart illustrating the preparation method of the antifouling high-flux reverse osmosis (RO) membrane provided in this embodiment of the invention;
[0034] Figure 2 This is a graph showing the application scenarios and flux relationship of the anti-fouling high-flux reverse osmosis (RO) membrane provided in this embodiment of the invention.
[0035] Figure 3 The diagram shows the operating time and flux recovery rate of the anti-fouling high-flux reverse osmosis (RO) membrane provided in this embodiment of the invention.
[0036] Figure 4 A diagram showing the heat treatment temperature and flux of an anti-fouling, high-flux reverse osmosis (RO) membrane provided in an embodiment of the present invention;
[0037] Figure 5 This is a graph showing the relationship between the concentration and flux of antifouling high-flux reverse osmosis (RO) membrane additives provided in an embodiment of the present invention.
[0038] Figure 6 The graph shows the relationship between the zeta potential and antifouling properties of the high-flux reverse osmosis (RO) membrane with antifouling properties provided in this embodiment of the invention. Detailed Implementation
[0039] The technical solution of the present invention will be further described below with reference to the accompanying drawings and specific embodiments.
[0040] The accompanying drawings are for illustrative purposes only and are schematic diagrams, not actual images. They should not be construed as limiting the scope of this application. To better illustrate the embodiments of the present invention, some parts in the drawings may be omitted, enlarged, or reduced, and do not represent the actual dimensions of the product. It is understandable to those skilled in the art that some well-known structures and their descriptions may be omitted in the drawings.
[0041] In the accompanying drawings of the embodiments of the present invention, the same or similar reference numerals correspond to the same or similar components. In the description of the present invention, it should be understood that if terms such as "upper," "lower," "left," "right," "inner," and "outer" indicate the orientation or positional relationship based on the orientation or positional relationship shown in the drawings, they are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, the terms used to describe positional relationships in the drawings are only for illustrative purposes and should not be construed as limiting the present application. For those skilled in the art, the specific meaning of the above terms can be understood according to the specific circumstances.
[0042] In the description of this invention, unless otherwise explicitly specified and limited, the term "connection" or similar designation indicating a connection between components should be interpreted broadly. For example, it can refer to a fixed connection, a detachable connection, or an integral part; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium; it can refer to the internal communication between two components or the interaction between two components. Those skilled in the art can understand the specific meaning of the above terms in this invention based on the specific circumstances.
[0043] Reference Figures 1-6 This application provides the following five embodiments and five comparative examples, wherein, Figure 1 The process of preparing a fouling-resistant, high-flux reverse osmosis (RO) membrane is demonstrated. Figure 2 The relationship between application scenarios and flux was demonstrated, and it was also shown that the flux in brackish water desalination scenarios was significantly higher than that in seawater desalination scenarios. Figure 3 The data shows the runtime and throughput recovery rate, and also indicates that the recovery rate remains above 93.5% after 2.5 months of operation. Figure 4 The relationship between heat treatment temperature and throughput was shown, and it was also indicated that 105-115℃ is the optimal temperature range. Figure 5 The relationship between additive concentration and flux was shown, and it was also shown that the flux performance was best in the concentration range of 0.8% to 1.2%. Figure 6 The relationship between zeta potential and antifouling properties was demonstrated, showing that the recovery rate exceeded 95% when the absolute value of the potential was >8mV; five specific examples and five comparative examples are as follows:
[0044] Example 1 - Preparation method is as follows:
[0045] Preparation of aqueous solution: Dissolve 3g of m-phenylenediamine and 1g of sodium tripolyphosphate in 96g of water to prepare an aqueous solution. At this time, the mass fraction of m-phenylenediamine is 3% and the mass fraction of sodium tripolyphosphate is 1%.
[0046] Preparation of oil phase solution: Dissolve 1g of trimesoyl chloride in 99g of n-hexane to obtain an oil phase solution with a mass fraction of 1% trimesoyl chloride.
[0047] Interfacial polymerization: The polysulfone support layer (120 μm thick, containing 2% by mass of nano-titanium dioxide particles) is immersed in an aqueous solution for 1.2 minutes. After removal, excess aqueous solution is scraped off, and the layer is quickly immersed in an oil solution for 35 seconds to carry out interfacial polymerization reaction and generate a polyamide separation layer.
[0048] Post-treatment: The membrane forming the polyamide separation layer was heat-treated at 105°C for 2.5 minutes, followed by rinsing with deionized water for 30 minutes to remove the additive complex. Subsequently, the membrane was immersed in a 1.5% (w / w) aqueous solution of sodium vinyl sulfonate and reacted at 45°C for 1.8 hours, allowing sodium vinyl sulfonate to be grafted onto the surface of the polyamide separation layer, forming antifouling functional groups containing sulfonic acid groups.
[0049] Technical effect
[0050] Precise control of the concentrations of the aqueous and oil phase solutions promotes a more complete interfacial polymerization reaction, resulting in a more uniform polyamide separation layer structure and improved membrane separation performance.
[0051] The additive sodium tripolyphosphate forms a complex with m-phenylenediamine, which forms a specific microstructure in the polyamide separation layer during subsequent removal, increasing the specific surface area of the membrane and helping to improve the flux.
[0052] The sulfonic acid antifouling functional groups formed by grafting sodium vinyl sulfonate enhance the hydrophilicity of the membrane surface, reduce pollutant adsorption, and improve antifouling performance.
[0053] Working principle
[0054] Polyamines in the aqueous solution and polyacrylamides in the oil solution meet on the surface of the support layer and undergo an interfacial polymerization reaction to form a polyamide separation layer.
[0055] The complex formed by the additive and the polyamine is removed during heat treatment and water washing, resulting in a porous structure in the polyamide separation layer, which facilitates the passage of water molecules.
[0056] The antifouling functional monomer sodium vinyl sulfonate is grafted onto the surface of the polyamide separation layer via a grafting reaction. Its sulfonic acid groups form hydrogen bonds with water molecules, reducing the membrane surface energy and decreasing pollutant adhesion.
[0057] Membrane performance test experimental data
[0058] The polyamide separation layer of the membrane is 110 nm thick, the surface roughness Ra is 0.35 nm, and the absolute value of the Zeta potential on the membrane surface is 8.5 mV.
[0059] In the simulated seawater desalination experiment, the influent pressure was 1.6 MPa, the influent NaCl concentration was 3.5%, the membrane flux reached 26 L / (m²・h), and the desalination rate was 98.5%.
[0060] After 1.2 months of continuous operation, chemical cleaning restored the membrane flux to 96% of its initial flux.
[0061] Example 2 - Preparation method is as follows:
[0062] Preparation of aqueous solution: Dissolve 2.5g p-phenylenediamine and 0.8g sodium hexametaphosphate in 96.7g water to obtain an aqueous solution with p-phenylenediamine mass fraction of 2.5% and sodium hexametaphosphate mass fraction of 0.8%.
[0063] Preparation of oil phase solution: Dissolve 1.2g of 2,4,6-trimethylbenzyl chloride in 98.8g of n-heptane to prepare an oil phase solution with a mass fraction of 1.2% for 2,4,6-trimethylbenzyl chloride.
[0064] Interfacial polymerization: First, the polysulfone support layer (130 μm thick, containing 1.5% by mass nano-titanium dioxide particles) is pretreated by immersing it in a 0.8% by mass silane coupling agent solution for 20 minutes. After being taken out and dried, it is immersed in an aqueous solution for 1.3 minutes. After removing the excess aqueous solution, it is immersed in an oil solution for 45 seconds to carry out interfacial polymerization.
[0065] Post-treatment: The membrane was heat-treated at 115°C for 2 minutes, then rinsed with deionized water for 30 minutes. After that, the membrane was immersed in a 2.5% (w / w) acrylic acid ethanol solution and reacted at 55°C for 1.2 hours to graft acrylic acid onto the surface of the polyamide separation layer, forming carboxyl-containing antifouling functional groups.
[0066] Technical effect
[0067] Pretreatment of the support layer enhances the adhesion to the polyamide separation layer and improves the mechanical stability of the membrane.
[0068] Optimized concentrations of polyamines and polyacrylic chlorides, along with reaction time, result in a denser and more uniform polyamide separation layer, improving desalination rate and throughput stability.
[0069] The carboxyl antifouling functional groups formed by acrylic acid grafting enhance the hydrophilicity and antifouling ability of the membrane, reducing dirt accumulation.
[0070] Working principle
[0071] The coupling agent forms active groups on the surface of the support layer, which form chemical bonds with the polyamide release layer, thereby enhancing the interlayer bonding.
[0072] When p-phenylenediamine and 2,4,6-trimethylbenzyl chloride are polymerized at the interface, a high-performance polyamide separation layer is generated by reacting them in an optimized ratio.
[0073] Acrylic acid undergoes a grafting reaction with the active sites on the surface of the polyamide separation layer at a certain temperature, exposing carboxyl groups on the membrane surface and improving the membrane surface properties.
[0074] Membrane performance test experimental data
[0075] The polyamide separation layer of the membrane is 130 nm thick, the surface roughness Ra is 0.42 nm, and the absolute value of the Zeta potential on the membrane surface is 9.2 mV.
[0076] In the brackish water desalination experiment, the influent pressure was 1.3 MPa, the influent NaCl concentration was 1%, and the membrane flux was 32 L / (m²). 2 •h), desalination rate 97.5%.
[0077] After 2.2 months of operation, chemical cleaning was performed, and the membrane flux recovery rate was 94%.
[0078] Example 3 - Preparation method is as follows:
[0079] Preparation of aqueous solution: Dissolve 1.8g m-phenylenediamine and 0.6g sodium tripolyphosphate in 97.6g water to obtain an aqueous solution with a mass fraction of 1.8% for m-phenylenediamine and 0.6% for sodium tripolyphosphate.
[0080] Preparation of oil phase solution: Dissolve 0.8 g of trimesoyl chloride in 99.2 g of n-hexane to prepare an oil phase solution with a mass fraction of 0.8% trimesoyl chloride.
[0081] Interfacial polymerization: The polysulfone support layer (110 μm thick, containing 2.5% nano-titanium dioxide particles by mass) is immersed in an aqueous solution for 1 minute, removed and the excess aqueous solution is scraped off. It is then immersed in an oil solution for 30 seconds to carry out an interfacial polymerization reaction to form a polyamide separation layer.
[0082] Post-treatment: The membrane forming the polyamide separation layer is heat-treated at 95°C for 3.5 minutes, rinsed with deionized water for 30 minutes, and then immersed in a 1% (w / w) aqueous solution of polyethylene glycol acrylate. The membrane is then reacted at 35°C for 2.5 hours to graft polyethylene glycol acrylate onto the surface of the polyamide separation layer, forming antifouling functional groups containing polyether segments.
[0083] Technical effect
[0084] Appropriate heat treatment temperature and time optimize the molecular structure of the polyamide separation layer and improve the chemical stability of the membrane.
[0085] The antifouling functional groups formed by grafting polyethylene glycol acrylate onto polyether segments endow the membrane with good antifouling properties and low surface roughness, thereby reducing membrane fouling.
[0086] The synergistic effect of aqueous and oil phase solution concentrations and reaction conditions ensures that the membrane has high flux and desalination rate.
[0087] Working principle
[0088] Heat treatment causes the molecular chains of the polyamide separation layer to rearrange, forming a more stable structure.
[0089] The double bonds of polyethylene glycol acrylate undergo a grafting reaction with the active groups on the surface of the polyamide separation layer, and the polyether segments extend on the membrane surface to form a hydrophilic and antifouling interface.
[0090] Reactants in aqueous and oil phase solutions react on the surface of the support layer under set conditions to construct a polyamide separation layer with specific separation properties.
[0091] Membrane performance test experimental data
[0092] The polyamide separation layer of the membrane is 90 nm thick, the surface roughness Ra is 0.28 nm, and the absolute value of the Zeta potential on the membrane surface is 7.8 mV.
[0093] In the simulated seawater desalination experiment, the influent pressure was 1.4 MPa, the influent NaCl concentration was 3.5%, the membrane flux was 23 L / (m²・h), and the desalination rate was 98.2%.
[0094] After 0.8 months of continuous operation, chemical cleaning restored the membrane flux to 95.5% of its initial flux.
[0095] Example 4 - Preparation method is as follows:
[0096] Preparation of aqueous solution: Dissolve 3.5g p-phenylenediamine and 1.2g sodium hexametaphosphate in 95.3g water to obtain an aqueous solution with p-phenylenediamine mass fraction of 3.5% and sodium hexametaphosphate mass fraction of 1.2%.
[0097] Preparation of oil phase solution: Dissolve 1.5g of 2,4,6-trimethylbenzyl chloride in 98.5g of n-heptane to prepare an oil phase solution with a mass fraction of 1.5% for 2,4,6-trimethylbenzyl chloride.
[0098] Interfacial polymerization: First, the polysulfone support layer (140 μm thick, containing 3% by mass nano-titanium dioxide particles) is pretreated by immersing in a 1.5% by mass titanate coupling agent solution for 25 minutes. After being taken out and dried, it is immersed in an aqueous solution for 1.5 minutes. After removing the excess aqueous solution, it is immersed in an oil solution for 50 seconds to carry out interfacial polymerization.
[0099] Post-treatment: The membrane was heat-treated at 108°C for 2.8 minutes, rinsed with deionized water for 30 minutes, and then immersed in a 3% (w / w) mixed solution of sodium vinyl sulfonate and acrylic acid (w / w) and reacted at 48°C for 2 hours to graft the two antifouling functional monomers onto the surface of the polyamide separation layer, forming antifouling functional groups containing sulfonic acid groups and carboxyl groups.
[0100] Technical effect
[0101] The support layer is pretreated with a titanate coupling agent, which significantly improves the bonding strength with the polyamide separation layer and extends the service life of the membrane.
[0102] By grafting mixed antifouling functional monomers, the advantages of sulfonic acid groups and carboxyl groups are combined to further enhance the hydrophilicity and antifouling properties of the membrane.
[0103] Optimized parameters for each step enable the membrane to achieve a better balance in flux, desalination rate, and antifouling performance.
[0104] Working principle
[0105] Titanate coupling agents form a bridge between the support layer and the polyamide separation layer, enhancing the interlayer interaction.
[0106] p-Phenylenediamine reacts with 2,4,6-trimethylbenzyl chloride to form a polyamide separation layer. Subsequently, sodium vinyl sulfonate and acrylic acid are grafted onto the surface of the separation layer, altering the chemical properties of the membrane surface.
[0107] The various reaction conditions work together to promote the formation of an ideal microstructure and surface properties in the membrane.
[0108] Membrane performance test experimental data
[0109] The polyamide separation layer of the membrane is 140 nm thick, the surface roughness Ra is 0.45 nm, and the absolute value of the Zeta potential on the membrane surface is 9.5 mV.
[0110] In the brackish water desalination experiment, the influent pressure was 1.4 MPa, the influent NaCl concentration was 1%, the membrane flux was 33 L / (m²・h), and the desalination rate was 97.8%.
[0111] After 2.5 months of operation, chemical cleaning was performed, and the membrane flux recovery rate was 93.5%.
[0112] Example 5 - Preparation method is as follows:
[0113] Preparation of aqueous solution: Dissolve 2.2g m-phenylenediamine and 0.9g sodium tripolyphosphate in 96.9g water to obtain an aqueous solution with a mass fraction of 2.2% for m-phenylenediamine and 0.9% for sodium tripolyphosphate.
[0114] Preparation of oil phase solution: Dissolve 1.1g of trimesoyl chloride in 98.9g of n-hexane to prepare an oil phase solution with a mass fraction of 1.1% trimesoyl chloride.
[0115] Interfacial polymerization: The polysulfone support layer (105 μm thick, containing 1.8% by mass of nano-titanium dioxide particles) was immersed in an aqueous solution for 1.1 minutes, removed and the excess aqueous solution was scraped off. The layer was then immersed in an oil solution for 32 seconds to carry out the interfacial polymerization reaction and form a polyamide separation layer.
[0116] Post-treatment: The membrane forming the polyamide separation layer is heat-treated at 102°C for 3 minutes, rinsed with deionized water for 30 minutes, and then immersed in a 2% (w / w) mixed solution of polyethylene glycol acrylate and sodium vinyl sulfonate (w / w) (w / w mass ratio 2:1). The mixture is reacted at 42°C for 2.2 hours to graft the two antifouling functional monomers onto the surface of the polyamide separation layer, forming antifouling functional groups containing polyether segments and sulfonic acid groups.
[0117] Technical effect
[0118] Grafting mixed antifouling functional monomers enriches the types of antifouling functional groups on the membrane surface, improving the diversity and effectiveness of antifouling.
[0119] Optimized solution concentration and reaction conditions ensure that the polyamide separation layer has good separation performance, while the grafting of antifouling functional groups does not affect the high-flux characteristics of the membrane.
[0120] The nano-titanium dioxide particles in the support layer work synergistically with the polyamide separation layer to improve the overall performance of the membrane.
[0121] Working principle
[0122] m-Phenylenediamine reacts with pyromellitic methyl chloride to form a polyamide separation layer, which is then grafted onto the surface of the separation layer with polyethylene glycol acrylate and sodium vinyl sulfonate.
[0123] Nano-titanium dioxide particles in the support layer enhance mechanical properties and provide a certain degree of photocatalytic anti-fouling effect, working synergistically with the anti-fouling function of the polyamide separation layer.
[0124] The reaction conditions control the formation of the membrane's microstructure, enabling the membrane to have high flux, high desalination rate, and strong antifouling properties.
[0125] Membrane performance test experimental data
[0126] The polyamide separation layer of the membrane is 100 nm thick, the surface roughness Ra is 0.32 nm, and the absolute value of the Zeta potential on the membrane surface is 8.2 mV.
[0127] In the simulated seawater desalination experiment, the influent pressure was 1.5 MPa, the influent NaCl concentration was 3.5%, the membrane flux was 24 L / (m²・h), and the desalination rate was 98.3%.
[0128] After 1.1 months of continuous operation, chemical cleaning restored the membrane flux to 95.8% of its initial flux.
[0129] Comparative Example 1 - Preparation method is as follows:
[0130] The reverse osmosis membrane was prepared according to the method of Example 1, except that the grafting reaction step in the post-treatment was not performed.
[0131] Technical effect
[0132] Because it lacks antifouling functional groups, the membrane surface has poor hydrophilicity, making it easy for pollutants to be adsorbed, resulting in poor antifouling performance.
[0133] The surface condition of the polyamide separation layer was not improved, and the roughness and zeta potential were not ideal, which affected the membrane flux and desalination rate, resulting in poor long-term operational stability.
[0134] Working principle
[0135] Only interfacial polymerization is performed to form a polyamide separation layer. No antifouling functional groups are used to change the membrane surface properties, and the separation and fouling mechanisms of conventional polyamide reverse osmosis membranes are followed.
[0136] Membrane performance test experimental data
[0137] The polyamide separation layer of the membrane is 100 nm thick, the surface roughness Ra is 0.62 nm, and the absolute value of the Zeta potential on the membrane surface is 12.5 mV.
[0138] Under the same simulated seawater desalination experimental conditions, the membrane flux was 20 L / (m²・h) and the desalination rate was 95%.
[0139] After one month of operation, the membrane flux decreased significantly, and chemical cleaning only restored it to 80% of the initial flux.
[0140] Comparative Example 2 - Preparation method is as follows:
[0141] The reverse osmosis membrane was prepared according to the method of Example 1, except that no additives were added to the aqueous solution.
[0142] Technical effect
[0143] The lack of additives to form complexes with polyamines and subsequent removal processes results in an undesirable microstructure and small specific surface area in the polyamide separation layer, leading to reduced membrane flux.
[0144] The controllability and uniformity of the interfacial polymerization reaction are affected, the quality of the polyamide separation layer decreases, and the desalination rate and antifouling performance also decrease accordingly.
[0145] Working principle
[0146] In the aqueous solution without additives, the polyamine reacts directly with the polyacrylamide chloride in the oil solution. The reaction process and the structure of the resulting polyamide separation layer are different from those when additives are added.
[0147] Membrane performance test experimental data
[0148] The polyamide separation layer of the membrane is 100 nm thick, the surface roughness Ra is 0.55 nm, and the absolute value of the Zeta potential on the membrane surface is 11 mV.
[0149] In the simulated seawater desalination experiment, the membrane flux was 22 L / (m²・h) and the desalination rate was 96%.
[0150] After one month of operation, the membrane flux recovered to 85% of the initial flux after chemical cleaning.
[0151] Comparative Example 3 - Preparation method is as follows:
[0152] The reverse osmosis membrane was prepared according to the method of Example 2, except that the support layer was not pretreated.
[0153] Technical effect
[0154] The weak bond between the support layer and the polyamide separation layer makes the membrane prone to delamination during use, affecting its mechanical stability and service life.
[0155] Insufficient binding force may cause changes in the internal structure of the membrane during operation, thereby affecting the stability of the membrane flux and desalination rate.
[0156] Working principle
[0157] The support layer is untreated and has few surface active sites. It bonds with the polyamide separation layer through physical action, and the bonding strength is much lower than that after pretreatment with coupling agent.
[0158] Membrane performance test experimental data
[0159] During operation, the membrane exhibited delamination in some areas.
[0160] In the brackish water desalination experiment, the initial membrane flux was 30 L / (m²・h) and the desalination rate was 97%. However, after 1.5 months of operation, the membrane flux dropped to 80% of the initial value and the desalination rate dropped to 95%. After chemical cleaning, the flux recovered to 88% of the initial flux.
[0161] Comparative Example 4 - Preparation method is as follows:
[0162] The reverse osmosis membrane was prepared according to the method of Example 3, except that the heat treatment temperature was 70°C.
[0163] Technical effect
[0164] If the heat treatment temperature is too low, the molecular chain rearrangement of the polyamide separation layer will be insufficient, resulting in poor chemical stability of the membrane, which will be susceptible to corrosion by chemical substances during use.
[0165] An imperfect molecular structure affects the pore structure and surface properties of the membrane, leading to a decrease in membrane flux and desalination rate, and also affecting its antifouling performance.
[0166] This includes performance optimization steps for antifouling high-flux reverse osmosis (RO) membranes. The performance optimization method for antifouling high-flux reverse osmosis (RO) membranes is to quantify the synergistic effect of antifouling functional group grafting density (G) and additive concentration (A) through the following equation:
[0167] ;
[0168] in:
[0169] K is the overall performance coefficient (dimensionless). The larger the value, the better the synergistic performance of membrane flux and antifouling.
[0170] A represents the mass fraction (%) of the additive in the aqueous solution.
[0171] G represents the grafting density (μmol / m²) of antifouling functional groups on the surface of the polyamide separation layer.
[0172] α is an interfacial polymerization regulating factor (ranging from 0.8 to 1.2), determined by the type of polyamine and polyacrylamide chloride;
[0173] β is the functional group efficiency factor (ranging from 1.5 to 2.5), which is determined by the hydrophilicity of the antifouling functional monomer.
[0174] Example: In Example 1:
[0175] A = 1% (sodium tripolyphosphate), G = 0.6 μmol / m 2 (Measured value);
[0176] m-phenylenediamine (MPD) and trimesoyl chloride (TMC) were selected, with α=1.0;
[0177] The antifouling monomer is sodium vinyl sulfonate (containing sulfonic acid groups), with β=2.0;
[0178] The calculation yields:
[0179] ;
[0180] Compared to the ungrafted control example 1 (G=0):
[0181] .
[0182] Technical effects:
[0183] 1. Performance prediction: When K>0.4, the membrane flux decay rate decreases by >40% (comparative example 1 decay rate 20% vs example 1 decay rate 4%).
[0184] 2. Process optimization: Maximize K by adjusting A and G (optimal interval K∈[0.45,0.55]) to avoid excessive grafting leading to flux reduction (e.g., G>1μmol / m). 2 time e -βG →0, but the separation layer swells and thickens).
[0185] 3. Material compatibility:
[0186] Hydrophilic monomers (such as sulfonic acid group β=2.0) are more efficient than weakly hydrophilic monomers (such as carboxyl group β=1.8);
[0187] Dense monomer combinations (such as the hybrid grafting in Example 4) enhance synergistic effects by increasing the β value.
[0188] Working principle and process:
[0189] 1. Pore creation using additives:
[0190] ln(1+A) ∝ Micropore specific surface area;
[0191] After the additive complex is removed, micropores are formed (e.g., Example 1 flux 26 L / (m²·h) vs Comparative Example 2 flux 22 L / (m²·h)).
[0192] 2. Functional groups resist pollution:
[0193] 1−e −βG ∝ Surface coverage;
[0194] Graft density G increases the surface roughness (Ra=0.35nm in Example 1) and the Zeta potential (∣ζ∣=8.5mV).
[0195] 3. Collaboration Mechanism:
[0196] Micropores provide water channels, and antifouling groups protect the micropores from clogging (as in Example 1, the flux recovered to 96% after cleaning). Equation K quantifies the dynamic balance between the two.
[0197] In summary, the working principle of the antifouling high-flux reverse osmosis (RO) membrane, its preparation method, and its application provided in this embodiment is as follows:
[0198] The core working principle of this antifouling, high-flux reverse osmosis (RO) membrane is based on the synergistic effect of interfacial polymerization and surface functionalization modification. First, the polyamine in the aqueous solution and the polyacrylamide in the oil solution undergo an interfacial polymerization reaction on the surface of the support layer to form a polyamide separation layer with separation function. This separation layer uses molecular sieving and charge repulsion to retain ions and pollutants in the water.
[0199] During the preparation process, the additives in the aqueous solution form complexes with the polyamines. After removal through subsequent treatment, a specific microstructure is formed in the polyamide separation layer, increasing the specific surface area of the membrane and providing more channels for water molecules to permeate, thereby improving flux. The pretreatment of the support layer enhances the bonding force between the support layer and the polyamide separation layer through coupling agents, ensuring the stability of the membrane structure.
[0200] In the post-treatment process, antifouling functional monomers are grafted onto the surface of the polyamide separation layer to form antifouling functional groups containing sulfonic acid groups, carboxyl groups, or polyether segments. These groups reduce the adsorption and deposition of pollutants by enhancing the hydrophilicity of the membrane surface, reducing surface roughness and the absolute value of the Zeta potential, thereby achieving an antifouling effect.
[0201] How to use
[0202] When using this membrane, the influent conditions must be controlled to ensure that the influent turbidity is less than 1 NTU and the SDI value is less than 5, in order to reduce the initial fouling of the membrane by influent contaminants. During the water treatment process, chemical cleaning is required every 1-3 months, using an acidic or alkaline cleaning agent with a pH of 2-12 (containing 0.1% to 2% surfactant by mass) to remove contaminants attached to the membrane surface and restore membrane performance.
[0203] Application scenarios cover seawater desalination, brackish water desalination, drinking water purification, and industrial wastewater reuse treatment. Depending on the characteristics of different water qualities, parameters such as operating pressure can be adjusted appropriately to achieve the best treatment effect.
[0204] The above are merely preferred embodiments of the present invention and are not intended to limit the implementation methods and protection scope of the present invention. Those skilled in the art should recognize that any equivalent substitutions and obvious changes made based on the description and illustrations of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a pollution resistant high flux reverse osmosis (RO) membrane, characterized in that, The method comprises the following steps: Preparation of an aqueous phase solution: mixing a polyamine, an additive and water to obtain an aqueous phase solution, the additive being a substance capable of forming a complex with the polyamine and being removable in subsequent processing, the mass fraction of the polyamine in the aqueous phase solution being 0.8% to 6%, and the mass fraction of the additive being 0.3% to 4%; Preparation of an oil phase solution: dissolving a polyacyl chloride in an organic solvent to obtain an oil phase solution, the mass fraction of the polyacyl chloride in the oil phase solution being 0.08% to 2.5%; Interfacial polymerization: coating the aqueous phase solution on the surface of a support layer, removing the excess aqueous phase solution after standing, then coating the oil phase solution, and performing interfacial polymerization to form a polyamide separation layer, the interfacial polymerization being performed for 10 to 60 seconds; Subsequent processing: performing heat treatment on the membrane after the formation of the polyamide separation layer, the heat treatment being performed at a temperature of 80 to 120℃ for 1 to 5 minutes, then rinsing the membrane with deionized water for 30 minutes to remove the complex formed by the additive and the polyamine, then immersing the membrane in a solution containing an anti-fouling functional monomer to enable the anti-fouling functional monomer to undergo grafting reaction with the surface of the polyamide separation layer, the grafting reaction being performed at a temperature of 20 to 60℃ for 0.5 to 3 hours to obtain the anti-fouling high-flux reverse osmosis (RO) membrane, the anti-fouling functional monomer being a compound containing at least one of a sulfonic acid group, a carboxyl group and a polyether segment.
2. The method of making a low-fouling high-flux reverse osmosis (RO) membrane according to claim 1, wherein, The polyamine is at least one of m-phenylenediamine and p-phenylenediamine, the additive is at least one of sodium hexametaphosphate and sodium tripolyphosphate, the mass fraction of the polyamine in the aqueous phase solution is 1% to 5%, and the mass fraction of the additive is 0.5% to 3%.
3. The method of making a low-fouling high-flux reverse osmosis (RO) membrane according to claim 1, wherein, The polyacyl chloride is at least one of trimesoyl chloride and 2,4,6-trimethylbenzene trimesoyl chloride, the organic solvent is at least one of n-hexane and n-heptane, and the mass fraction of the polyacyl chloride in the oil phase solution is 0.1% to 2%.
4. The method of making a low-fouling high-flux reverse osmosis (RO) membrane according to claim 1, wherein, The anti-fouling functional monomer is at least one of sodium vinyl sulfonate, acrylic acid and polyethylene glycol acrylate.
5. The method of making a low-fouling high-flux reverse osmosis (RO) membrane according to claim 1, wherein, Before the interfacial polymerization step, the method further comprises a step of pretreating the support layer, the pretreatment being immersing the support layer in a solution containing a coupling agent, the coupling agent being at least one of a silane coupling agent and a titanate coupling agent, the mass fraction of the coupling agent solution being 0.1% to 2%, and the immersion time being 5 to 30 minutes.
6. A high flux reverse osmosis (RO) membrane against pollution, prepared by the method according to any one of claims 1 to 5, characterized in that, The anti-fouling high-flux reverse osmosis (RO) membrane comprises a support layer and a polyamide separation layer arranged on the surface of the support layer, the surface of the polyamide separation layer being grafted with anti-fouling functional groups having hydrophilicity and anti-fouling properties, the anti-fouling functional groups being groups containing at least one of a sulfonic acid group, a carboxyl group and a polyether segment formed after the grafting of an anti-fouling functional monomer, the surface roughness Ra of the polyamide separation layer being less than 0.5 nm, and the absolute value of the Zeta potential of the membrane surface being less than 10 mV.
7. The anti-fouling, high-flux reverse osmosis (RO) membrane of claim 6, wherein, The support layer is a polysulfone support layer, the thickness of the polysulfone support layer being 50 to 150 μm, and the polysulfone support layer containing nano titanium dioxide particles with a mass fraction of 0.5% to 3%.
8. The anti-fouling, high-flux reverse osmosis (RO) membrane of claim 6, wherein, The thickness of the polyamide separation layer is 50-200 nm, and the grafting density of the anti-fouling functional group on the surface of the polyamide separation layer is 0.1-1 μmol / m².
9. Use of the anti-fouling high-flux reverse osmosis (RO) membrane according to any one of claims 6-8 in seawater desalination, brackish water desalination, drinking water purification, and industrial wastewater reuse treatment.
10. Use according to claim 9, characterized in that, In the water treatment using the anti-fouling high-flux reverse osmosis (RO) membrane, the turbidity of the feed water is less than 1 NTU, the SDI value is less than 5, and during the treatment, the membrane is chemically cleaned every 1-3 months, the cleaning agent used in the chemical cleaning is an acid or alkaline cleaning agent with a pH value of 2-12, and the cleaning agent contains a surfactant with a mass fraction of 0.1%-2%.
Citation Information
Cited By
High-flux anti-fouling composite reverse osmosis membrane, and preparation method and application thereof
CN122252039A